218k views
0 votes
Please Answer and Show your Work:

4x/13 + 3/13 = -1/13

User Samarey
by
5.0k points

1 Answer

2 votes

Answer:

x = -1

Explanation:

Note that all terms have 13 in the denominator. In such a case as this, you can remove the denominators (only when each and EVERY one of them are the same is this possible).

4x/13 + 3/13 = -1/13 ⇒ 4x + 3 = -1

Simplify. Isolate the variable, x. Do the opposite of PEMDAS. Note the equal sign, what you do to one side, you do to the other.

Subtract 3 from both sides.

4x + 3 = -1

4x + 3 (-3) = -1 (-3)

4x = -1 - 3

4x = -4

Divide 4 from both sides.

(4x)/4 = (-4)/4

x = (-4)/4

x = -1

-1 is your answer for x.

~

User MasterPlanMan
by
5.0k points